2016
DOI: 10.3727/096368916x691691
|View full text |Cite
|
Sign up to set email alerts
|

Generation of Equine-Induced Pluripotent Stem Cells and Analysis of Their Therapeutic Potential for Muscle Injuries

Abstract: Horse health has become a major concern with the expansion of horse-related industries and sports; the importance of healthy muscles for horse performance and daily activities is undisputed. Here we generated equineinduced pluripotent stem cells (E-iPSCs) by reprogramming equine adipose-derived stem cells (E-ADSCs) into iPSCs using a polycistronic lentiviral vector encoding four transcription factors (i.e., Oct4, Sox2, Klf4, and c-Myc) and then examined their pluripotent characteristics. Subsequently, establis… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

2
33
0

Year Published

2017
2017
2023
2023

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 27 publications
(35 citation statements)
references
References 42 publications
2
33
0
Order By: Relevance
“…The derivation of equine iPSCs was first reported in 2011 (44) where a piggyback transposon system was used containing murine Oct4, Sox2, Klf4, and Myc reprogramming factors. This has then been followed by several other publications over the last 5 years , the majority of which have used viral expression vectors to mediate integration of the reprogramming gene sequences. Following reprogramming to a pluripotent state the viral transgenes should become silenced .…”
Section: Induced Pluripotent Stem Cells In Companion Animalsmentioning
confidence: 99%
See 1 more Smart Citation
“…The derivation of equine iPSCs was first reported in 2011 (44) where a piggyback transposon system was used containing murine Oct4, Sox2, Klf4, and Myc reprogramming factors. This has then been followed by several other publications over the last 5 years , the majority of which have used viral expression vectors to mediate integration of the reprogramming gene sequences. Following reprogramming to a pluripotent state the viral transgenes should become silenced .…”
Section: Induced Pluripotent Stem Cells In Companion Animalsmentioning
confidence: 99%
“…Our group has been working to understand the factors which control tendon differentiation of equine ESCs and predifferentiating them prior to use may help to reduce the risk of teratoma formation. The derivation of horse and dog iPSCs has been conducted by more groups than ESC derivation, with successful teratoma formation being described in several publications . However, there are a few reported attempts to generate teratomas with canine iPSCs which failed .…”
Section: Characterizing Pluripotent Stem Cellsmentioning
confidence: 99%
“…In contrast to mesenchymal stem cells that have been used for tissue regeneration in the last decade [2][3][4], iPSCs have the advantages of indefinite proliferation and higher differentiation potential [5]. In fact, equine iPSCs myogenic differentiation capability has already been probed for skeletal muscle regeneration [6].…”
Section: Introductionmentioning
confidence: 99%
“…Several groups have reported the generation of iPSCs in the horse by reprogramming adult fibroblasts, fetal fibroblasts, keratinocytes and adipose-derived stem cells [6][7][8][9]. With these reports, it is clear that equine iPSCs can be generated from different sources, with the capacity to differentiate into all three germinal layers both in vitro and in vivo.…”
Section: Introductionmentioning
confidence: 99%
“…Compared to humans, the availability of iPSCs (and specially ESCs) from horses is limited, as is the number of studies reporting their differentiation into functional cell types (Donadeu, 2014 ). A previous study showed the generation of myosin heavy chain (MyHC)-positive myotubes from equine skeletal muscle cell-derived iPSCs (Quattrocelli et al, 2016 ), whereas another reported formation of muscle fibers after transplantation of equine adipose stem cell-derived iPSCs into injured skeletal muscle of mice (Lee et al, 2016 ). In the present study, we took a step further by generating functional myocytes from equine iPSCs and comparing their characteristics with those of myocytes produced from adult equine skeletal muscle precursors.…”
Section: Introductionmentioning
confidence: 99%